ARHGEF15 overexpression worsens the prognosis in patients with pancreatic ductal adenocarcinoma through enhancing the motility and proliferative activity of the cancer cells. Issue 1 (December 2016) - Fukushima, Hiroto; Yasumoto, Makiko; Ogasawara, Sachiko; Akiba, Jun; Kitasato, Yuhei; Nakayama, Masamichi; Naito, Yoshiki; Ishida, Yusuke; Okabe, Yoshinobu; Yasunaga, Masafumi; Horiuchi, Hiroyuki; Sakamoto, Etsuko; et al.
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive neoplastic diseases, associated with a remarkably poor prognosis. However, the molecular mechanisms underlying the development of PDAC remain elusive. The aim of this study was to identify genes whose expressions are correlated with a poor prognosis in PDAC patients, and to unravel the mechanisms underlying the involvement of these genes in the development of the cancer. Methods Global gene expression profiling was conducted in 39 specimens obtained from Japanese patients with PDAC to identify genes whose expressions were correlated with a shorter overall survival. The effect of gene silencing or overexpression of ARHGEF15 in pancreatic cancer cell lines was examined by introducing siRNAs of ARHGEF15 or the ARHGEF15 expression vector. After assessing the effect of ARHGEF15 deregulation on the Rho-family proteins by pull-down assay, wound healing, transwell and cell viability assays were carried out to investigate the cellular phenotypes caused by the perturbation. Results The global mRNA expression profiling revealed that overexpression of ARHGEF15, a Rho-specific GEF, was significantly associated with a poor prognosis in patients with PDAC. We also found that the depletion of ARHGEF15 by RNA interference in pancreatic cancer cell lines downregulated the activities of molecules of the Rho signaling pathway, including RhoA, Cdc42 and Rac1. Then, we also showed that ARHGEF15 silencing significantly reduced the motility and viability of the cells, while its overexpression resulted in the development of the opposite phenotype in multiple pancreatic cancer cell lines. Conclusion These data suggest that upregulation of ARHGEF15 contributes to the development of aggressive PDAC by increasing the growth and motility of the pancreatic cancer cells, thereby worsening the prognosis of these patients. Therefore, ARHGEF15 could serve as a novel therapeutic target in patients with PDAC.